Cross‐cultural equivalence of parental ratings of child difficulties during the pandemic: Findings from a six‐site study. Issue 1 (22nd August 2022) - Foley, Sarah; Ronchi, Luca; Lecce, Serena; Feng, Xin; Chan, Meingold H. M.; Hughes, Claire
Abstract: Objectives: The Strengths and Difficulties Questionnaire (SDQ) has been shown to be invariant across informants, developmental stage and settings, but tests of cross‐cultural equivalence are limited to adolescents' self‐reports. The COVID‐19 pandemic makes this gap particularly pertinent, given the need to understand whether distinct government approaches (e.g., school closures) are uniquely associated with variability in children's psychosocial outcomes and the reliance on parents' ratings for young children. Methods: Within a Confirmatory Factor Analysis framework, we tested the cross‐cultural measurement invariance of the SDQ across six countries: Australia, China, Italy, Sweden, the United Kingdom and USA, using a sample of 1761 parents of 3‐ to 8‐year‐olds ( M = 5.76, SD = 1.09). Results: A five‐factors model showed good fit to the data and partial cross‐cultural scalar invariance. In this sample, Swedish parents reported the fewest peer problems (Cohen's d = 0.950) and the highest prosocial scores (Cohen's d = 0.547), whilst British parents reported the greatest child emotional (Cohen's d = 0.412) and hyperactivity problems (Cohen's d = 0.535). Conclusions: The present results indicate that the parent‐version of the SDQ is appropriate for use and comparison across different contexts during the pandemic.